2022
DOI: 10.3389/fnut.2022.1000510
|View full text |Cite
|
Sign up to set email alerts
|

Combining mussel with fucoidan as a supplement for joint pain and prediabetes: Study protocol for a randomized, double-blinded, placebo-controlled trial

Abstract: IntroductionPharmaceutical drugs are beneficial to inflammatory conditions but with side effects, which led to the search for alternative therapies. Perna canaliculus, the New Zealand green-lipped mussel, have shown promise in placebo-controlled trials for inflammatory conditions. Fucoidan, an extract from seaweed Undaria pinnatifida, has been found to have beneficial effects on joint pain and insulin resistance. However, green-lipped mussel and fucoidan have never been combined.Methods and analysisA parallel,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…33 Based on current toxicological research, the administration of a high dose of fucoidan at 2000 mg/kg/day through oral gavage in rats has not exhibited any indications of adverse reactions. 10 Furthermore, clinical trials have revealed potential advantages of low-dose fucoidan, making it a viable choice for treating conditions like asthma, 34 diabetes 35 and serving as adjunctive therapy for cancer. 36 Considering its protective effect on the cardiovascular system and its low toxicity, 37 we speculate that fucoidan can also be used in the clinical treatment of hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…33 Based on current toxicological research, the administration of a high dose of fucoidan at 2000 mg/kg/day through oral gavage in rats has not exhibited any indications of adverse reactions. 10 Furthermore, clinical trials have revealed potential advantages of low-dose fucoidan, making it a viable choice for treating conditions like asthma, 34 diabetes 35 and serving as adjunctive therapy for cancer. 36 Considering its protective effect on the cardiovascular system and its low toxicity, 37 we speculate that fucoidan can also be used in the clinical treatment of hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of fucoidan to obese non-diabetic patients did not affect glycemia, insulin levels, or insulin resistance compared to controls (ACTRN12614000495628) [167], and no effect of a fucoidan-rich extract from the algae Ascophyllum nodosum was observed on postprandial glucose levels or insulin response in normoglycemic subjects (NCT05460884) [168]. Another clinical study with fucoidan treatment is ongoing on prediabetic individuals (ACTRN12621000413820) [169], which will allow us to define its antidiabetic potential in a more clinically relevant population. A study including healthy participants on the impact of polyphenol-rich brown seaweed (Fucus vesiculosus) extract showed no effect on glycemia or insulin levels (ACTRN12616000126415p) [170], as well as the intake of the Undaria pinnatifida algae (containing fucoidan, fucoxanthin, and polyphenols) in a healthy population, while a hypoglycaemic effect was observed after administration of its sporophylls, likely due to the higher fibre content [171].…”
Section: Marine Compounds Under Clinical Trial For T2dm Treatmentmentioning
confidence: 99%